Associations of Dysnatremia with COVID-19 Status and Mortality. Issue 8 (25th August 2022) - Liu, Diane; Mowrey, Wenzhu; Fisher, Molly; Basalely, Abby; McCarthy, John; Kumar, Neelja; Thakkar, Jyotsana; Azzi, Yorg; Brogan, Maureen; Golestaneh, Ladan; Reidy, Kimberly J; Chen, Wei
Key Points: Dysnatremias were more common in patients with coronavirus disease 2019 (COVID-19) than in those without COVID-19. Hypernatremia in patients with COVID-19 was associated with higher mortality than eunatremia. Visual Abstract: Abstract : Background: In patients without COVID-19, dysnatremia is associated with mortality. These relationships are not well established in patients with COVID-19. We tested the hypotheses that patients with COVID-19 were more likely to have dysnatremia than those without COVID-19 and that, among those with COVID-19, dysnatremia is associated with mortality. Methods: We conducted a retrospective observational study of patients admitted to a tertiary care center in the Bronx, New York, during the COVID-19 surge from March 11 to April 26, 2020. Using multinomial logistic regression models, we compared the prevalence of hypernatremia (serum sodium ≥150 mEq/L) and hyponatremia (serum sodium <130 mEq/L) on admission between patients with and without COVID-19. Among patients with COVID-19, we used Cox proportional hazards models to examine the association of dysnatremia with mortality. Results: Compared with those without COVID-19 ( n =1265), patients with COVID-19 ( n =3345) had a higher prevalence of hypernatremia (7% versus 4%, P <0.001) and hyponatremia (7% versus 6%, P =0.04). In adjusted models, COVID-19-positive patients had a higher likelihood of having hypernatremia (adjusted odds ratio=1.87, 95% CI, 1.3 to 2.57, P =0.001) compared with COVID-19-negative patients, whereas the association between hyponatremia and COVID-19 status was no longer significant ( P =0.06). Among patients with COVID-19, 775 (23%) died after a median follow-up of 17 days (IQR 7–27 days). Among nonsurvivors, 15% had hypernatremia and 8% had hyponatremia on admission. Hypernatremia was associated with a higher risk of mortality (adjusted hazard ratio=1.28, 95% CI, 1.01 to 1.63, P =0.04) compared with patients with eunatremia. Conclusions: In patients hospitalized during the spring 2020 COVID-19 surge, COVID-19 status was associated with hypernatremia on admission. Among patients with COVID-19, hypernatremia was associated with higher mortality. Hypernatremia may be a potential prognostic marker for mortality in COVID-19 patients.